Wealth Effects in Europe : A Tale of Two Countries (Italy and the United Kingdom) - Munoz, Sonia (IMF Working Papers; Working Paper, 2006)
This paper investigates the increasing exposure of European households to risky financial assets and the consequent impact on the economy. I analyze household data for Italy and the United Kingdom, countries that differ dramatically in their financial structure and capital markets. I estimate an endogenous switching model with bivariate switching to overcome two important obstacles in this line of research, namely, the consumption Capital Asset Pricing Model Puzzle and the excess sensitivity puzzle. The results show that there are wealth effects in both countries. I find some evidence of liquidity constraints only in Italy and habit formation exclusively in the United Kingdom.